2014
DOI: 10.1097/eja.0b013e328365ae28
|View full text |Cite|
|
Sign up to set email alerts
|

Intravenous nonopioid analgesic drugs in chronic low back pain patients on chronic opioid treatment

Abstract: The present data show that the anticipation of an i.v. infusion of nonopioid analgesic drug improves VAS significantly, probably through expectation-related mechanisms. However, single dose i.v. infusions of nonopioid analgesic drugs fail to improve pain intensity and spinal mobility in CLBP patients on chronic opioid treatment, even immediately after the infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The median treatment duration in included trials was 7 (IQR, 5–7) days. NSAIDs were mostly administered orally, but five trials used intravenous or intramuscular injection,35 37–39 59 and three used a topical formulation, such as a gel, patch or cream 51 53 56. Nine trials had a three-arm parallel design and two were randomised crossover trials.…”
Section: Resultsmentioning
confidence: 99%
“…The median treatment duration in included trials was 7 (IQR, 5–7) days. NSAIDs were mostly administered orally, but five trials used intravenous or intramuscular injection,35 37–39 59 and three used a topical formulation, such as a gel, patch or cream 51 53 56. Nine trials had a three-arm parallel design and two were randomised crossover trials.…”
Section: Resultsmentioning
confidence: 99%
“…While the efficacy of acetaminophen in spinal pain was statistically significant in a recent meta‐analysis, the greatest observed effect size of −3.7 points in a 0–100 point VAS scale falls short of the minimal clinically relevant change of −9.0 points . However, unlike our study, this review included patients presenting acute pain conditions , and studies using single‐dose regimens . Extrapolating data from single‐dose or intermediate duration treatment regimens (treatment duration less than 3 months) to that of chronic use (more than 6 months continuous treatment) is questionable as earlier studies have shown loss of analgesic efficacy during long‐term follow‐up .…”
Section: Discussionmentioning
confidence: 88%
“…For example, pre-emptive diclofenac resulted in favorable analgesia immediately following spinal surgery but those patients that received diclofenac also required a greater quantity of analgesic drugs at significantly higher doses during the post-operative period than patients who received only a continuous infusion of morphine [47]. More recently, administration of diclofenac was shown to provide minimal enhancement in pain relief in patients that were treated with opioids for non-cancer chronic lower back pain even when diclofenac was infused at the same time as morphine [48]. These clinical observations underscore the importance of our present study, which was designed to establish a mechanistic basis for drug-drug interactions between NSAIDs and opioid analgesic drugs.…”
Section: Discussionmentioning
confidence: 99%